Step-by-step explanation:
Simplifying
(7a + 3b)(7a + -3b) = 0
Multiply (7a + 3b) * (7a + -3b)
(7a * (7a + -3b) + 3b * (7a + -3b)) = 0
((7a * 7a + -3b * 7a) + 3b * (7a + -3b)) = 0
Reorder the terms:
((-21ab + 49a2) + 3b * (7a + -3b)) = 0
((-21ab + 49a2) + 3b * (7a + -3b)) = 0
(-21ab + 49a2 + (7a * 3b + -3b * 3b)) = 0
(-21ab + 49a2 + (21ab + -9b2)) = 0
Reorder the terms:
(-21ab + 21ab + 49a2 + -9b2) = 0
Combine like terms: -21ab + 21ab = 0
(0 + 49a2 + -9b2) = 0
(49a2 + -9b2) = 0
Solving
49a2 + -9b2 = 0
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '9b2' to each side of the equation.
49a2 + -9b2 + 9b2 = 0 + 9b2
Combine like terms: -9b2 + 9b2 = 0
49a2 + 0 = 0 + 9b2
49a2 = 0 + 9b2
Remove the zero:
49a2 = 9b2
Divide each side by '49'.
a2 = 0.1836734694b2
Simplifying
a2 = 0.1836734694b2
take the square root of each side:
a = {-0.428571429b, 0.428571429b}
<h2>
The slope intercept form of the given equation is: y = 2x + ( - 20) </h2>
Step-by-step explanation:
Given,
The equation y + 18 = 2( x - 1)
To write the given equation in the slope intercept form = ?
∴ The equation y + 18 = 2( x - 1)
⇒ y + 18 = 2x - 2
⇒ y = 2x - 2 - 18
⇒ y = 2x - 20
⇒ y = 2x + ( - 20) ..... (1)
We know that,
The equation of slope intercept form,
y = mx + c
Where, m is the sope and c is the y-intercept
∴ The slope intercept form of the given equation is: y = 2x + ( - 20)
Answer:
six uniys to left of 3 is= +2,+1,0,-1-2-3
three unit right of 15is= +16,+17, +18
Eight unit to the left of =-4,-5,-6,-8,-9,-10,-11,-12
seven units ti right of -5=-3,-2,-1,0+1,+2,+3,+4
Answer:
Option (D) is correct.
No, They will not intersect.
Step-by-step explanation:
Given Points for g(x), (1,2) , (2,4) and (3,6)
Since g is a linear function then it must be in form of g(x) = mx +c where, c is constant and m is slope.
We first calculate the slope using,
![m=\frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
Here, consider ![x_1=1 , x_2=2 , y_1=2, y_2=4](https://tex.z-dn.net/?f=x_1%3D1%20%2C%20x_2%3D2%20%2C%20y_1%3D2%2C%20y_2%3D4)
Substitute above, we get slope as,
![m=\frac{4-2}{2-1}=2](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B4-2%7D%7B2-1%7D%3D2)
Thus, equation becomes g(x) = 2x + c ...(1)
For c plug the values in (1),
(1,2) ⇒ 2= 2 + c ⇒ c = 0
Thus, Equation of G(x) is 2x.
When we plot it it do not intersect f(x).
Thus, Option (D) is correct.
No, They will not intersect.
Hello from MrBillDoesMath!
Answer:
a(n) = 12 - 3(n-1) , n = 1,2,3.,,
Discussion:
The terms are 12, 9, 6, 3 so we are apparently subtracting 3 from each succeeding term. . Hence
a(n) = 12 - 3(n-1) , n = 1,2,3.,,
Thank you,
MrB